2021
DOI: 10.3390/cancers13164017
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Radioligand Therapy with Repeated Cycles of 177Lu-PSMA-617 in Metastatic Castration-Resistant Prostate Cancer with Diffuse Bone Marrow Involvement

Abstract: Advanced stage metastatic prostate cancer with extensive bone marrow involvement is associated with a high risk of therapy-induced myelotoxicity and unfavorable outcomes. The role of salvage radioligand therapy (RLT) with 177Lu-PSMA-617 in this subset of patients remains to be further elucidated. Forty-five patients with progressive metastatic castration-resistant prostate cancer (mCRPC) and diffuse bone marrow involvement were treated with repeated cycles of RLT after having exhausted standard treatment optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The significance of initial PSA response (≥50% after 4 weeks) to 177 Lu-PSMA-617 as a positive predictor of outcome remains controversial. A few studies in heterogeneous patient cohorts showed a longer OS in patients with early PSA response [13,21,25], whereas other studies reported no significantly longer survival in early responders [23,26]. In a study by Leibowitz et al on 24 elderly patients at >75 years of age, 14 of whom previously treated with 223 Ra, a PSA decline of ≥ 50% was associated with a significantly longer OS (10.9 vs. 3.1 months, p = 0.0006) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of initial PSA response (≥50% after 4 weeks) to 177 Lu-PSMA-617 as a positive predictor of outcome remains controversial. A few studies in heterogeneous patient cohorts showed a longer OS in patients with early PSA response [13,21,25], whereas other studies reported no significantly longer survival in early responders [23,26]. In a study by Leibowitz et al on 24 elderly patients at >75 years of age, 14 of whom previously treated with 223 Ra, a PSA decline of ≥ 50% was associated with a significantly longer OS (10.9 vs. 3.1 months, p = 0.0006) [13].…”
Section: Discussionmentioning
confidence: 99%
“…For example, 177Lu-PSMA-617 can accurately deliver radiation to PSMA-positive PCa cells without damaging surrounding healthy tissues. As a result, RLT effectively prolongs the OS of advanced CRPC and bone metastasis, significantly delaying the progression of disease symptoms (28)(29)(30).…”
Section: Effects Of Several Therapeutic Methods On the Survival Rate ...mentioning
confidence: 99%
“…A constant challenge to treating prostate cancer is acquired resistance to hormone therapy and treatment with docetaxel [ 6 ]. Many patients with advanced cancer become unresponsive to ADTs, referred to as having metastatic castration-resistant prostate cancer (mCRPC) which has shown positive treatment response with lutetium-177 ( 177 Lu)-prostate-specific membrane antigen (PSMA)-617 [ 6 ]. It is a radioligand therapy that uses a β-emitting radioisotope lutetium-177 which is added to the ligand PSMA-617.…”
Section: Introductionmentioning
confidence: 99%
“…An increase or decrease in prostate-specific antigen (PSA) levels from a baseline value is used to determine treatment success or failure [ 4 ]. Several studies included in this review reported notable decreases in PSA levels [ 6 , 8 , 9 , 10 ]. Further, studies that examined the efficacy and safety of 177 Lu-PSMA-617 proved it to be promising [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation